Exploration of Waria Jargon in The Movie “Lovely Man” as Representation - Fauzi, Aziz; Prima Sintasari, Diardana; Fajrin, Verawati; Sudarmaji, Imam (International Proceedings of Nusantara Raya, 2024)
Social life always forms such diverse activities, it is because community groups form the same consciousness as several people so that they form social groups. This research will discuss the variations of language used by the transvestite group in the movie "Lovely Man". The focus of this research is to find out the use of waria language in the movie "Lovely Man" and analyze the meaning and meaning of the variety of languages used. The method used is a descriptive qualitative method. The method is used by researchers to analyze in depth the phenomenon that occurs. The results showed that there were 10 variations of jargon used by the transvestite group in the movie "Lovely Man". The variation of the jargon can occur due to the social and psychological conditions of the transvestites. Transvestites prefer to use non-standard vocabulary so that many basic words are changed by them into variations that are typical among transvestites.